The Effectiveness of Kegel Exercises in Reducing Urinary Incontinence in Post-Operative TURP Patients - Junaidin Junaidin; Rizki Nugraha Agung; Dewi Anggraini; Wati Jumaiyah (Indonesian Journal of Global Health Research, 2025)
Urinary incontinence is a common complication following Transurethral Resection of the Prostate (TURP) for benign prostatic tumors, which significantly impacts the quality of life of patients. Kegel exercises have been proven effective as a non-pharmacological intervention to improve bladder control and strengthen the pelvic floor muscles. This study aims to evaluate the effectiveness of Kegel exercises in reducing urinary incontinence levels in post-TURP patients. Objective to assess the effectiveness of Kegel exercises in reducing the severity of urinary incontinence in post-TURP patients. This study used a quasi-experimental design with a pre-test and post-test approach on 15 post-TURP patients at RSUD Labuang Baji Makassar. Respondents performed Kegel exercises for 7 days with a frequency of 6 sessions per day. Urinary incontinence levels were measured using the ICIQ-UI Short Form questionnaire before and after the intervention. Data analysis was conducted using the dependent t-test. Before the intervention, the average urinary incontinence score was 24.27 (±2.712), which decreased to 21.73 (±3.217) after the intervention, with a p-value of < 0.001. The effect size of 0.915 indicates a significant effect. Kegel exercises are effective in reducing the severity of urinary incontinence in post-TURP patients. This intervention is recommended as a non-pharmacological therapy to improve patients' quality of life.